2012
DOI: 10.1190/geo2011-0507.1
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the electrical conductivity of hydrogeological strata using joint-inversion of loop-loop electromagnetic data

Abstract: In coastal-estuarine agricultural landscapes that are inherently rich in sulfidic sediments and saline water-tables, natural resource management data need to be collected to describe the heterogeneous nature of the soil, underlying regolith, and interactions with groundwater. Geophysical methods, such as electromagnetic (EM) induction instruments, are increasingly being used. This is because they measure apparent soil electrical conductivity [Formula: see text], which has previously been successfully used to m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The main reasons are that the instruments do not require physical contact with the soil and there are an ever‐increasing number of commercially available instruments that provide information about the soil (i.e., EM38 and DUALEM‐1), vadose zone (e.g., EM31 and DUALEM‐2), and deeper regolith (e.g., EM34). Electromagnetic induction instruments are also easy to set‐up, use and mobilize (e.g., Triantafilis et al, 2012). Electromagnetic induction instruments measure the apparent soil electrical conductivity (ECa), which has been shown to be influenced by various soil (e.g., clay and mineralogy) and hydrological (e.g., moisture) properties which are of high agricultural value.…”
Section: Proximal Soil Sensingmentioning
confidence: 99%
See 1 more Smart Citation
“…The main reasons are that the instruments do not require physical contact with the soil and there are an ever‐increasing number of commercially available instruments that provide information about the soil (i.e., EM38 and DUALEM‐1), vadose zone (e.g., EM31 and DUALEM‐2), and deeper regolith (e.g., EM34). Electromagnetic induction instruments are also easy to set‐up, use and mobilize (e.g., Triantafilis et al, 2012). Electromagnetic induction instruments measure the apparent soil electrical conductivity (ECa), which has been shown to be influenced by various soil (e.g., clay and mineralogy) and hydrological (e.g., moisture) properties which are of high agricultural value.…”
Section: Proximal Soil Sensingmentioning
confidence: 99%
“…To understand soil and hydrogeological interactions, Triantafilis et al (2012) jointly‐inverted EMI data collected across an estuarine or alluvial landscape using both the DUALEM‐421 and EM34 instruments. Figure 1 shows that the joint‐inversion of ECa data obtained from both of these instruments produces reasonably robust estimates of the true electrical conductivity.…”
Section: Proximal Soil Sensingmentioning
confidence: 99%
“…Given that any electromagnetic (EM) method in the low frequency range [16] is diffusive and integrates a large volume based on the footprint of the system, this approach will inevitably smoothen out real soil structures. A few authors have suggested to perform a full inversion of the EMI data without assuming the LIN approximation [29][30][31], but it is our impression that this is not common practice. For airborne instruments of a similar type, the industry standard has been to perform a full processing and inversion of the data [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The number of iterations are specified or continue until the misfit between observed apparent conductivity (σnormalanormalo ) and calculated apparent conductivity (σnormalanormalc ) is reduced to an acceptable level. Incorporating a Lagrangian multiplier ( λ ), also called a damping factor, achieves this in balancing data fit and closeness to the a priori initial earth model (Triantafilis et al ).…”
Section: Methodsmentioning
confidence: 99%
“…The number of iterations are specified or continue until the misfit between observed apparent conductivity (σ o a ) and calculated apparent conductivity (σ c a ) is reduced to an acceptable level. Incorporating a Lagrangian multiplier (λ), also called a damping factor, achieves this in balancing data fit and closeness to the a priori initial earth model (Triantafilis et al 2012). Evaluation of the optimum λ value is able to be performed empirically through comparison of models of contrasting λ with expected responses from the literature and sample validation procedures (Monteiro .…”
Section: Inversion Modelingmentioning
confidence: 99%